Perimortem trauma in King Richard III: a skeletal analysis. Issue 9964 (17th January 2015) - Appleby, Jo; Rutty, Guy N; Hainsworth, Sarah V; Woosnam-Savage, Robert C; Morgan, Bruno; Brough, Alison; Earp, Richard W; Robinson, Claire; King, Turi E; Morris, Mathew; Buckley, Richard
Summary: Background: Richard III was the last king of England to die in battle, but how he died is unknown. On Sept 4, 2012, a skeleton was excavated in Leicester that was identified as Richard. We investigated the trauma to the skeleton with modern forensic techniques, such as conventional CT and micro-CT scanning, to characterise the injuries and establish the probable cause of death. Methods: We assessed age and sex through direct analysis of the skeleton and from CT images. All bones were examined under direct light and multi-spectral illumination. We then scanned the skeleton with whole-body post-mortem CT. We subsequently examined bones with identified injuries with micro-CT. We deemed that trauma was perimortem when we recorded no evidence of healing and when breakage characteristics were typical of fresh bone. We used previous data to identify the weapons responsible for the recorded injuries. Findings: The skeleton was that of an adult man with a gracile build and severe scoliosis of the thoracic spine. Standard anthropological age estimation techniques based on dry bone analysis gave an age range between 20s and 30s. Standard post-mortem CT methods were used to assess rib end morphology, auricular surfaces, pubic symphyseal face, and cranial sutures, to produce a multifactorial narrower age range estimation of 30–34 years. We identified nine perimortem injuries to the skull and two to the postcranial skeleton. We identified no healed injuries. The injuries were consistent with those created by weapons from the later medieval period. We could not identify the specific order of the injuries, because they were all distinct, with no overlapping wounds. Three of the injuries—two to the inferior cranium and one to the pelvis—could have been fatal. Interpretation: The wounds to the skull suggest that Richard was not wearing a helmet, although the absence of defensive wounds on his arms and hands suggests he was still otherwise armoured. Therefore, the potentially fatal pelvis injury was probably received post mortem, meaning that the most likely injuries to have caused his death are the two to the inferior cranium. Funding: The University of Leicester.